Climate change perceptions, expectations, observations, and projections at Lake Victoria - Stefan Liersch; Karlijn van den Broek; Tobias Pilz; Usman Isyaku; Maryse Chappin; Gisela Böhm; Bwambale Mbilingi; Joseph Luomba; Fonda Jane Awuor; Robert Kayanda; Shigalla Mahongo; Charles Ogunbode; et al. (Environmental Research Communications)
Understanding people's perceptions of climate change and associated environmental risks is paramount in assessing how individuals respond to climate change. Awareness of the consequences of climate change determines the present and future behaviours and expectations, as well as the actions taken to mitigate the likely impacts. We surveyed the perceived and expected climate change consequences of experts and community members in the Lake Victoria basin in East Africa, compared them with hydro-meteorological observations and projections, and established that some perceived trends, such as increasing temperature or rainfall intensity, correspond with meteorological observations. However, the perceived increase in drought occurrence (believed to be a recent consequence), was not substantiated by the meteorological data. It was only in the northwestern region that drought frequency increased since the year 2000, while the rest of the basin did not experience such a trend. Community members were concerned about the already noticeable consequences of climate change on their livelihoods through agriculture or fishing, while experts were mainly focused on the amplification of hazards such as floods and droughts. This divergence may imply that experts underestimate the consequences that society is already facing. Nevertheless, both groups expect that climate change will undoubtedly lead to the deterioration of human well-being by affecting food security, increasing poverty, and increasing the incidence of disease. This is a serious concern that requires immediate attention. Such insights into people's climate change perceptions can help policy-makers, researchers, and community members to better tailor adaptation solutions acceptable to the local context. Effective governance is essential to enable people to adapt to climate change and other challenges, including those resulting from the impacts of globalisation, demographic trends, and the degradation and scarcity of resources.